Chemogenetic ON and OFF switches for RNA virus replication - Heilmann, Emmanuel; Kimpel, J.; Hofer, B.; Rössler, A.; Blaas, I.; Egerer, L.; Nolden, T.; Urbiola, C.; Kräusslich, Hans-Georg; Wollmann, G.; Laer, Dorothee von (Nature Communications, 2021)
Therapeutic application of RNA viruses as oncolytic agents or gene vectors requires a tight control of virus activity if toxicity is a concern. Here we present a regulator switch for RNA viruses using a conditional protease approach, in which the function of at least one viral protein essential for transcription and replication is linked to autocatalytical, exogenous human immunodeficiency virus (HIV) protease activity. Virus activity can be en- or disabled by various HIV protease inhibitors. Incorporating the HIV protease dimer in the genome of vesicular stomatitis virus (VSV) into the open reading frame of either the P- or L-protein resulted in an ON switch. Here, virus activity depends on co-application of protease inhibitor in a dose-dependent manner. Conversely, an N-terminal VSV polymerase tag with the HIV protease dimer constitutes an OFF switch, as application of protease inhibitor stops virus activity. This technology may also be applicable to other potentially therapeutic RNA viruses.